A Novel Pyroptosis-Related Gene Signature for Predicting Prognosis in Kidney Renal Papillary Cell Carcinoma - Hu, Jian; Chen, Yajun; Gao, Liang; Ge, Chengguo; Xie, Xiaodu; Lei, Pan; Zhang, Yuanfeng; Liang, Peihe (Frontiers in Genetics, 2022)
Pyroptosis was defined as an inflammatory form of programmed cell death. Increasing studies have demonstrated that pyroptosis was closely related to tumor development and antitumor process. However, the role of pyroptosis in kidney papillary cell carcinoma (KIRP) remains obscure. In this study, we analyzed the expression of 52 pyroptosis-related genes (PRGs) in KIRP, of which 20 differentially expressed PRGs were identified between tumor and normal tissues. Consensus clustering analysis based on these PRGs was used to divided patients into two clusters, from which a significant difference on survival was found (p=0.0041). The prognostic risk model based on 6 PRGs (CASP8, CASP9, CHMP2A, GPX4, IL6, and IRF1) was built using univariate Cox regression and LASSO–Cox regression analysis, with a good performance in predicting 1-, 3-, and 5-year overall survival. Kaplan–Meier survival analysis showed that the high-risk group had a poor survival outcome (P<0.001), and risk score was an independent prognostic factor (HR: 2.655, 95%CI 1.192-5.911, P=0.016). Immune profiling revealed differences in immune cell infiltration between two groups, and the infiltration of M2 macrophage was significantly upregulated in the tumor immune microenvironment, implying that tumor immunity participated in the KIRP progression. Finally, we identified 2 hub genes in tumor tissues (IL6 and CASP9), which were validated in vitro. In conclusion, we conducted a comprehensive analysis of PRGs in KIRP, and tried to provide a pyroptosis-related signature for predicting the prognosis.